Dordt and Pentecostal traditions: African 'Spiritual' Churches in South Africa today - Mbaya, Henry (In die Skriflig, 2019)
This article explores the possible link between the teachings of the Canons of Dordt in the Netherlands (1618–1619) and those of the Pentecostal and African Spiritual Churches in South Africa today. This article tries to identify some common features as well as points of divergence between the two traditions, particularly with regard to the role of Scripture, divine sovereignty, and human responsibility in salvation. Secondly, this study highlights the views on the role of the Holy Spirit in election and salvation in relation to divine grace.
Free
Keywords: African Traditions; Arminians; BIBLE; CHURCH buildings; Canons; Christian; Doctrine; Dordrecht; Dordt Synod; Dutch; HOLY Spirit; MANNERS & customs; NETHERLANDS; PENTECOSTALISM; Pentecostalism; Reformed Faith; SALVATION; SOUTH Africa; Salvation; Scripture